P032 SURGICAL SITE INFECTIONS FOLLOWING EMERGENCY HERNIA REPAIR: A SUB-STUDY FROM THE MASH PROJECT. (25th November 2021) - Proctor, Victoria; Spence, Olivia; Burns, Flora; Green, Susanna; Sayers, Adele; Smart, Neil; Lee, Matthew
Abstract: Aim: Acutely symptomatic hernia (ASH) of the abdominal wall and groin are common presentations. Decisions related to repair technique can be driven by contamination and surgical site infection (SSI) risk. The aim of this study is to report rates of SSI following ASH repair, and assess the performance of the Bluebelle wound health questionnaire in this population. Material and Methods: This study reports on the operated sub-group of the MASH study. This was a 12 week, UK-based, multi-centre, collaborative, prospective cohort study (NCT04197271) recruited adults with ASH. Hernia site, repair type, wound complications, and Bluebelle questionnaire at 30 & 90 days were captured. Performance of this score was assessed using ROC curves, and regression modelling. Results: 223 patients were operated on, and 21 (9.4%) developed SSI within 90 days. Infections were most common in umbilical hernia (16.2%). No infections were seen in 'simple' symptomatic hernia. There was no association with either repair type. Bluebelle scores for 109 patients had an area under the curve of 0.807, showing good performance in this population. Regression modelling showed that SSI was most strongly associated with increased Bluebelle score (OR 8.54 (4.27 to 12.80, p < 0.001)). Use of a sutured repair was associated with a lower score (OR -3.79 (-7.19 to -0.39, p = 0.029)). Conclusions: SSI is common after surgical treatment of ASH. Strategies to reduce this are needed. The Bluebelle score appears valid for this population; mesh repair might affect scores independent of SSI.